The influence of transformational leadership for environmental sustainability on organizational citizenship behaviors - da Silva Wegner, Roger; de Fátima Barros Estivalete, Vania; Keila Matheis, Taiane; Mendes Vieira, Kelmara (Review of Business Management, 2025)
Purpose – To investigate the influence of transformational leadership for the environment (TLE) in the context of Brazilian industries, testing the hypothesis that workers engage in organizational citizenship behaviors (OCBs) through organizational citizenship behaviors for the environment (OCB-Es). Theoretical framework – Transformational leadership for the environment and voluntary behaviors are essential elements for developing more efficient environmental management (Asghar et al., 2022; Li et al., 2022). Design/methodology/approach – Using the perceptions of 1068 workers, a structural equation model (SEM) was created to test the hypotheses. Findings – The results obtained in this study reveal four main findings. (1) TLE significantly influences OCB-Es. (2) TLE has a direct influence on OCBs; (3) OCB-Es significantly influence OCBs. (4) OCB-Es moderate the indirect influence of TLE on OCBs. Practical & social implications of the research – It was noted that there is a need for Brazilian organizations to develop policies and practices aimed at people management and its interface with environmental management, enabling the qualification of workers in the topics and pointing to sustainability in the work environment. In addition, the constructs studied are useful for understanding workers’ perceptions of environmental performance, stimulating actions aimed at environmental improvement and providing opportunities for training that leads to the resolution of problems related to the environment. Originality/value – The study offers suggestions to help leaders promote voluntary cooperative behavior among their subordinates, thereby reducing the pollution caused by Brazilian industries.